2018
DOI: 10.1155/2018/8249180
|View full text |Cite
|
Sign up to set email alerts
|

Saliency Detection by Multilevel Deep Pyramid Model

Abstract: Traditional salient object detection models are divided into several classes based on low-level features and contrast between pixels. In this paper, we propose a model based on a multilevel deep pyramid (MLDP), which involves fusing multiple features on different levels. Firstly, the MLDP uses the original image as the input for a VGG16 model to extract high-level features and form an initial saliency map. Next, the MLDP further extracts high-level features to form a saliency map based on a deep pyramid. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…After the learning feature ends in the deep convolutional network, a small number of tagged data input networks are used to fine-tune the parameters, and the network is continuously optimized. 17,21,26,27,28 The output of the fully connected layer k can be obtained by weighting the inputs and by the effect of the activation function…”
Section: Deep Convolutional Networkmentioning
confidence: 99%
“…After the learning feature ends in the deep convolutional network, a small number of tagged data input networks are used to fine-tune the parameters, and the network is continuously optimized. 17,21,26,27,28 The output of the fully connected layer k can be obtained by weighting the inputs and by the effect of the activation function…”
Section: Deep Convolutional Networkmentioning
confidence: 99%
“…ere are several ways to extract the highlighted area of the image, including [15][16][17][18][19][20][21][22]. In [15], a new classification scheme is presented which combines CNN and visual attention mechanism; Shariatmadar and Faez [16] proposed a model that combines the bottom-up and top-down features to extract the prominent part of the image; He et al, in [17], extended Itti's model by using structure tensor; Luo et al [18] identified the salient object based on backbone enhanced network; Yang et al [19] detected the salient part of the image by introducing the double-random-walks; in [20], the BU and TD features of a single image are used to detect salient region; Wang et al, in [21], proposed a model of saliency detection related to multilevel deep pyramid (MLDP), and finally, in [22], the diver target detection is performed based on a saliency detection method.…”
Section: Introductionmentioning
confidence: 99%
“…Saliency object detection can provide the mask of wildlife for the progressive transmission process, which is utilized to separate the object and background information. Conventional saliency detection algorithms, such as the human-computer interaction [ 18 ], visual attention model [ 19 ] and multilevel deep pyramid model [ 20 ] have undesired algorithm complexity issues.…”
Section: Introductionmentioning
confidence: 99%